Dehydration and Hemodynamic Changes as Causa Mortis Associated with Trichuris vulpis in a Dog - Silva, Eric Arantes da; Oliveira, Igor Borges; da Silva, Thâmara Rossi Martins; Amaral, Andreia Vitor Couto do; Meirelles-Bartoli, Raphaella Barbosa; Braga, Ísis Assis; Saturnino, Klaus Casaro; Ramos, Dirceu Guilherme de Souza (Acta Scientiae Veterinariae, 2021)
Background: Trichuris vulpis, a species that belongs to Trichuris and shows a cosmopolitan distribution, parasitizes the gastrointestinal system of dogs causing trichuriasis. The infection occurs owing to ingestion of larval eggs and subsequent fixation of their adult form in the large intestine of the host. The objective of this paper is to report the case of a Border Collie dog that arrived at the Veterinary Pathology Laboratory (LPV) of the Federal University of Jataí (UFJ) after exhibiting signs of intense dehydration and sudden death caused by severe T. vulpis infection, and to elucidate the macroscopic and microscopic histopathological correlations observed during necropsy. Case: A 7-year-old male Border Collie dog was referred for routine necroscopic examination on suspicion of death from intoxication. In the history, there were reports of bone ingestion, restlessness, and polydipsia for three days, followed by sudden death. Although the animal presented an adequate body state during the necroscopic procedure, enophthalmia and pale oral and ocular mucosa were observed, which are characteristic signs of severe dehydration and anemia. On opening the abdominal cavity, the visceral serosa were found to be stained and severely dry. Greenish mucous content was observed throughout the intestine, and in the large intestine, a moderate amount of mucus associated with high parasitic infestation by elongated parasites attached to the mucosa was identified. The parasites were harvested, stored in airtight vials containing 70% alcohol, processed, and subsequently identified as T. vulpis. Discussion: The necroscopic findings associated with the histopathology were compatible with T. vulpis infestation at high parasite intensity, with severe destruction of the intestinal mucosa and inability of water absorption, resulting in severe dehydration. In cases of parasitism, villous atrophy with crypt hypertrophy occurs, a fact observed in the present case. Possibly crypt hypertrophy occurs prior to villous atrophy, and occurs independently of previous lesions of the absorptive compartment. This results in poor absorption. Advanced loss of gastrointestinal tract fluids can usually be extensive and lead to progressive dehydration with loss of isotonic and hypertonic fluids, which can also be observed in the observation of blood components, severely accelerating changes such as hypovolemia and posterior hemoconcentration. Hypovolemia from severe dehydration also decreases renal perfusion and reduces the rate of glomerular filtration. Hypovolemia also leads to decreased blood pumping capacity, which may lead to heart failure and pulmonary circulatory disorders with notable effects on gas exchange, which may cause hypoxemia and possibly lethal metabolic acidosis. The necropsy performed on the animal found a severe dehydration that could be sustained mainly owing to signs of hypovolemia, associated with a series of pathophysiological events with the massive presence of parasites identified as T. vulpis. The damage caused to the intestinal mucosa by the oral stylet, the movement, and toxins of the parasites led to a severe condition of villosities destruction and tissue necrosis, leading to a large loss of the absorption function of nutrients in the intestines and especially of water, resulting in a condition of severe dehydration. This imbalance of system functioning also alters cardiac function because of increased blood viscosity generating possible lardaceous clots, which in turn are indicative of anemia. This cycle of deleterious changes can result in hypovolemic shock and consequent sudden death.